Global trends in migraine and anxiety over the past 10 years: a bibliometric analysis - Biao Huang; Weining Chen; Chunmei Peng; Yu Wang; Xiuli Shen; Qi Zhang; Liu Yang; Jun Wu (Frontiers in Neurology)
BackgroundRecent studies have shown that migraine significantly increases the incidence of anxiety and is positively correlated with the severity and frequency of migraine. The relationship between migraine and anxiety has attracted extensive attention. This study focused on the association between migraine and anxiety, aiming to predict potential future research trends.MethodsA bibliometric analysis was conducted using publications from the Core Collection of Web of Science. We utilized CiteSpace.5.8.R3 and VOSviewer 1.6.17 to evaluate the value of articles over the past 10 years.ResultsThe number of publications has increased significantly over the past 10 years. The cooperative network analysis shows that the United States is the most collaborative country. Additionally, Harvard University is the institution and Richard B. Lipton the individual with the highest number of studies on migraine. The analysis of keyword outbreaks indicates that the strong citation burst words are closely related to sex differences, activation, allodynia, and preventive treatment, which represent emerging new research areas and potential hotspots for future research.ConclusionAn overall upward trend in the research of migraine and anxiety was observed. Sex differences, functional magnetic resonance imaging (fMRI), activation, allodynia, and preventive treatment are predicted to be hotspots in the future.